Implementasi Program Double Track di SMA Raden Fatah Gresik Studi Kasus dalam Meningkatkan Keterampilan dan Kewirausahaan Siswa - Siska Purnamasari (PT. Nawa Edukasi Nusantara, 2025)
This qualitative case study research explores the planning, implementation, and evaluation of the Double Track program at SMA Raden Fatah Gresik, a private high school in the suburban area of Gresik Regency, East Java. The program, initiated by the East Java Provincial Government, aims to equip students with vocational skills and entrepreneurial competencies, particularly for those not pursuing higher education. Data were collected through in-depth structured interviews with school principals, program coordinators, trainers, and students, complemented by participatory observation and analysis of program documentation. Thematic analysis based on the interactive model of Miles and Huberman (1992) revealed that program planning involves two key stages: departmental selection aligned with local potential and student mapping focusing on non-college-bound students. Program implementation emphasizes a 40% theory and 60% practice approach, conducted outside regular hours, and is strengthened through strategic partnerships with local businesses, industries (DUDI), and MSMEs. Evaluation mechanisms include practical product-based exams, competency certification, and monitoring of student entrepreneurial initiatives post-graduation. Findings indicate that the Double Track program has successfully enhanced students' practical skills in fashion design, culinary arts, and multimedia, fostered an entrepreneurial mindset, and improved the school's image within the community. However, challenges such as limited funding, facility constraints, and the need for more certified trainers persist. This study concludes that the Double Track model is an effective strategy for bridging the gap between academic education and labor market demands, contributing to reduced graduate unemployment and promoting youth economic independence.